All eyez on me: Disproportionality, disciplined, and disregarded while Black. Issue 3 (3rd July 2022) - Hines, Erik M.; Ford, Donna Y.; Fletcher, Edward C.; Moore, James L.
ABSTRACT: In this article, we present an extensive overview of inequities in three areas of education: (1) gifted and talented education; (2) accelerated coursework; (3) and discipline. Intersectionality undergirds our focus on these three areas as they go together to paint a disturbing picture of the experiences of Black children in P-12 schools, as well as institutions of higher education. In addition to laying out the culturally assaultive problems, we provide recommendations and resources designed to develop anti-racist, culturally competent educators, along with an equitable education system where Black students are seen as capable, intelligent, good citizens, and humans who are understood and affirmed; thus, " All Eyez on Me " results in dynamic rather than deficit thinking among education professionals.